Rapeseed oil‑rich diet alters hepatic mitochondrial membrane lipid composition and disrupts bioenergetics - Monteiro, João P. (2013)
Diet is directly related with physiological alterations occurring at a cell and subcellular level. However, the role of diet manipulation on mitochondrial physiology is still largely unexplored. Aiming at correlating diet with alterations of mitochondrial membrane composition and bioenergetics, Wistar-Han male rats were fed for 11, 22 and 33 days with a rapeseed oil-based diet and mitochondrial bioenergetics, and membrane composition were compared at each time point with a standard diet group. Considerable differences were noticed in mitochondrial membrane lipid composition, namely in terms of fatty acyl chains and relative proportions of phospholipid classes, the modified diet inducing a decrease in the saturated to unsaturated molar ratio and an increase in the phosphatidylcholine to phosphatidylethanolamine molar ratio. Mass spectrometry lipid analysis showed significant differences in the major species of cardiolipin, with an apparent increased incorporation of oleic acid as a result of exposure to the modified diet. Rats fed the modified diet during 22 days showed decreased hepatic mitochondrial state 3 respiration and were more susceptible to Ca2+-induced transition pore opening. Rapeseed oil-enriched diet also appeared to promote a decrease in hydroperoxide production by the respiratory chain, although a simultaneous decrease in vitamin E content was detected. In conclusion, our data indicate that the rapeseed oil diet causes negative alterations on hepatic mitochondrial bioenergetics, which may result from membrane remodeling. Such alterations may have an impact not only on energy supply to the cell, but also on drug-induced hepatic mitochondrial liabilities.